2020
DOI: 10.1093/rheumatology/kez630
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of tocilizumab in refractory Takayasu arteritis: final results of the randomized controlled phase 3 TAKT study

Abstract: Objective To investigate the long-term efficacy and safety of the IL-6 receptor antibody tocilizumab in patients with Takayasu arteritis (TAK). Methods Patients completing the randomized, double-blind, placebo-controlled period of the TAKT (Takayasu arteritis Treated with Tocilizumab) trial were followed up during open-label extended treatment with weekly s.c. tocilizumab 162 mg for up to 96 weeks or longer, with oral glucoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 17 publications
3
44
0
2
Order By: Relevance
“…An analysis of a case series of 5 patients plus a review 39 patients reported from the literature showed no effect of TCZ on radiological activity on imaging (defined as at least two of the following: (1) arterial wall thickening in angio-CT, (2) or arterial wall thickening with wall strengthening in MRA, (3) by PET-CT) after 6 months [76]. However, a significant decrease in arterial FDG uptake in PET-CT was demonstrated [76], which, in accordance with the long-term data of the prospective study [75], suggests that TCZ reduces inflammation in the vessel wall but does not necessarily lead to an improvement in structural vascular lesions.…”
Section: Biologic Therapiessupporting
confidence: 87%
See 1 more Smart Citation
“…An analysis of a case series of 5 patients plus a review 39 patients reported from the literature showed no effect of TCZ on radiological activity on imaging (defined as at least two of the following: (1) arterial wall thickening in angio-CT, (2) or arterial wall thickening with wall strengthening in MRA, (3) by PET-CT) after 6 months [76]. However, a significant decrease in arterial FDG uptake in PET-CT was demonstrated [76], which, in accordance with the long-term data of the prospective study [75], suggests that TCZ reduces inflammation in the vessel wall but does not necessarily lead to an improvement in structural vascular lesions.…”
Section: Biologic Therapiessupporting
confidence: 87%
“…Since 44% of the patients receiving TCZ relapsed (vs. 61.1% on placebo), which resulted in an increase in the GC dose, no GC-sparing effect of TCZ could be shown during the blinded part of the study. However, during the long-term extension phase, in which 28 patients received open-label TCZ, the median GC dose was reduced from 0.223 mg/kg/day (study start) to 0.131 mg/kg/day (interquartile range 0.099, 0.207) after 48 weeks and 0.105 mg/kg/ day (interquartile range 0.039, 0.153) after 96 weeks [75]. On imaging, 17.9% of patients showed improvement and 67.9% stable findings without progression at 96 weeks.…”
Section: Biologic Therapiesmentioning
confidence: 99%
“…However, in a minority of patients with relapsing/refractory TAK, pro-inflammatory cytokines such as TNF-α, IL-6, IL-17, and IFN-γ likely exert a pathogenic role and should therefore be therapeutically addressed. This is the goal of TNF-α inhibitors, such as etanercept, infliximab, adalimumab, and certolizumab [8,[62][63][64], as well as anti-interleukin (IL)-6 receptor monoclonal antibodies such as tocilizumab [65][66][67][68], which are increasingly being administered. However, controlled clinical studies in a suitable number of patients are required to allow definitive conclusions about the efficacy of these agents.…”
mentioning
confidence: 99%
“…Akiyama et al have presented a thorough literature review and have described a positive and efficacious effect of tocilizumab in 11 cases of refractory polyarteritis nodosa (PAN) described in 6 case series. Indeed, the use of tocilizumab, an interleukin (IL)-6 inhibitor, in vasculitis is gaining evidence in the literature, specifically in large vessel vasculitis including giant cell arteritis and Takayasu arteritis 3 4. Nevertheless, it should be noted that although the IL-6 pathway is the major inducer of STAT 3, and therefore was used by us in vitro to stimulate this pathway in order to evaluate STAT 3 activation, clinically blocking the IL-6 pathway in our patient, using tocilizumab, was not beneficial, contrasting with our positive result with tofacitinib.…”
mentioning
confidence: 86%